Effect Of Leadership, Organizational Behavior And Motivation Working of The Effectiveness Performance In Department Revenue Regional Bogor - Sundoro, Bagus Yudo; Hubeis, Musa; Indupurnahayu, Indupurnahayu (Jurnal Manajemen, 2015)
Leadership is one of the most important factors to build good organisation character including raising motivation to the worker so that the affectivity from the worker can be achieved. This reseach use multiple regression to know the influence of independent variable leadership, organiasation attitude, work motivation to the effectivity of wroking. The data gain use program IBM SPSS 19. The result of the resource shows that leadership variable has influance to positive significant 38%, attitude variabel organisation influance to positive 67,6%, and motivation variable works influance 53,9% to the effectivity of workers job . Leadership variabel organisation attitude, work motivation as together influance is 72,4% to the effectivity of working and the rest 27,6% is explained by another variable that do not conduct.